ANALISIS GAYA BELAJAR DAN PERILAKU BISNIS PENGUSAHA KECIL BIDANG AGRIBISNIS DI KOTA KENDARI - Rianse, Usman; Abdullah, Weka Gusmiarty; Alwi, La Ode (Jurnal AGRISEP, 2013)
The absence of information regarding business learning styles and behavior of small entrepreneurs in the agribusiness field in Kendari city can lead to less precise determination of creative economic policy in the Kendari city. This study aims to: determine the type of business learning style and behavior of small entrepreneurs in the agribusiness field in Kendari city. Analysis of learning styles performed by calculating the level of rank (from left to right) was made by the respondents to the questionnaire that has been provided based on the level of compatibility with the learning behavior of respondents. Analysis of the entrepreneurs’s behavior carried out by observing the dominance of respondents’s answering on the questionnaire (19 questions) that have been provided. The results showed that learning style of the small entrepreneurs in the agribusiness field in Kendari city spread into 4 (four) types of learning styles, in the following order: 38.89% assimilator type, 27.78% converger type, 16.67% respectively for acomodator and diverger type. Business behavior of small entrepreneurs in the agribusiness field in Kendari city clustered on the behavior of III (100%), nomely the ethical business behavior (clean businness). Among that entrepreneurs who behave 100% clean business behavior, there were 38.89% of entrepreneurs who conduct very strong (high) clean business and 61.11% who conduct rather low clean business.